OPTIMASI PRODUKSI SUMUR “ZL” DENGAN MENGGUNAKAN ARTIFICIAL LIFT ELECTRICAL SUBMERSIBLE PUMP PADA LAPANGAN “YY” - Erizaldi Musthofa Sudjito; Andi Jumardi; Firdaus Firdaus (PETROGAS: Journal of Energy and Technology, 2021)
The well "ZL" is located in the Tarakan field which at the beginning of production did not use an Artificial Lift. However, these wells will experience a decrease in production rates due to lower reservoir pressure and increased water cut levels. An Artificial Lift is needed to help lift the fluid to the surface. The Artificial Lift chosen for the “ZL” well is the Electrical Submersible Pump. In the initial step of ESP design, the method used was appropriate to the field conditions "YY", namely the Vogel Method. Next determine the amount of pump efficiency (% EP) and perform optimization on the ESP pump by changing the operating frequency. The “ZL” well has a maximum flow rate of 3347.9 BFPD with a target flow rate of 2343.53 BFPD. Based on the target flow rate in the “ZL” well, it is recommended to use a REDA D2400N 60Hz pump. Furthermore, from the optimization results at a frequency of 50 Hz, a production rate of 1180.8 BFPD with 59% EP was obtained, at a frequency of 55 Hz, a production rate of 1659.6 BFPD with 66% EP was obtained, at a frequency of 60 Hz a production rate of 2346.8 BFPD was obtained with % EP 68%, at a frequency of 65 Hz the production rate was 2846.2 BFPD with% EP 64%, and at a frequency of 70 Hz the production rate was 3266.4 BFPD with% EP 60%. From the results obtained that the frequency of 60 Hz with a production rate of 2346.8 BFPD and% EP 68% were selected based on Best Efficiency.